In vitro antileishmanial and antioxidant potential, cytotoxicity evaluation and phytochemical analysis of extracts from selected medicinally important plants. (May 2019) - Mehwish, Shaila; Islam, Arshad; Ullah, Ikram; Wakeel, Abdul; Qasim, Muhammad; Khan, Mubarak Ali; Ahmad, Ayaz; Ullah, Nazif
Abstract: The antileishmanial drugs presently available have stern limitations regarding efficiency, safety and cost that make it crucial to hunt for novel therapeutic approaches from natural products. In current study crude methanolic extracts (CMEs) of four medicinally important plants were evaluated for their phytochemical constituents, antioxidant potentials, cytotoxicity and antileishmanial activities. Digera muricata (L) and Cannabis sativa (Linn) showed highest total phenolic and flavonoid content (273.4 μg GAE/mg DW and 206.8 μg QA/mg DW, respectively), amongst others. Total antioxidant capacity determined in vitro by phosphomolybdenum assay exhibited that Saccharum spontaneum (L) and Mangifera indica (L) were the strongest antioxidants (∼108 and ∼100 μg AAE/g of DW, respectively) plants amongst other tested. The S. spontaneum showed remarkable scavenging activity (EC50 44.9 μg/mL), while M. indica showed to possess the lowest scavenging activity (EC50 105.7 μg/mL) on 1, 1-diphenyl-2-picrylhydrazyl. S. spontaneum and C. sativa were the least toxic (CC50, 113.0 and 109.4 μg/mL respectively), while M. indica remained the most toxic (CC50 42.46 μg/mL). Moreover, the in vitro evaluation of antileishmanial potential of plants CMEs, demonstrated a dose-dependent growth inhibition of L. major promastigotes and axenic amastigotes. M. indica and D. muricate extracts exhibited to possess antileishmanial potential at minute concentrations (IC50 5.2 and 18.9 μg/mL, respectively) comparable to that of tartar emetic (IC50 4.7μg/mL) against L. major promastigotes. Each CME was significantly active ( p < 0.0001) against L. major axenic amastigotes when compared to Glucantime ® . This study encourages the isolation of bioactive compounds from these plants for antileishmanial drug development.